Identification of chemical compounds from agarwood hydrosol (Aquilaria malaccensis) fruits via LC-QTOF-MS/MS analysis - Mohamad Azharishah, Satar; Nurul Waheeda, Abdu Rahman; Mohd Aizudin, Abd Aziz; K, M Isa
Gaharu hydrosol is being considered as a by-product produced during the hydrodistillation of resinous wood part of Aquilaria spp. Agarwood hydrosol was reported to possess many bioactive compounds that are beneficial for health. However, current studies on the chemical composition of agarwood hydrosol from the fruit part are still lacking. This research presents the untargeted chemical compound of agarwood hydrosol from Aquilaria malaccensis fruit (AF) via liquid chromatography quadrupole time of flight mass spectrometry (LC-QTOFMS/MS) and comparison the active functional groups with industrial hydrosol grade using Fourier transform infrared (FTIR). Qualitative tandem LC-QTOF-MS/MS was utilised to identify compounds in the extracted sample. The data processing revealed the presence of 128 known compounds in the hydrosol from A. malaccensis fruit in negative ionization mode and only one chemical profile detected after switched to positive ionization mode. This result contains the retention times value of m/z [M - H-], [M + HCOO-], [M + H+] and similar database search hit identities of the 129 compounds detected during the LC-QTOFMS/MS analysis in Table A1 and A2